(untitled) (Research, Society and Development, 2020)
Smoking is associated with unfavorable outcomes in COVID-19. Smokers are more vulnerable to respiratory viruses than non-smokers, with a greater risk of serious influenza infection in smokers, who also have more severe clinical conditions. With this, the present research aims to describe the main risks of the relationship between smoking and COVID-19. This is an integrative review. To carry out this study, the following databases were consulted: Medical Literature Analysis and Retrieval System Online (MEDLINE), Google Scholar and Scientific Eletronic Library Online (SCIELO). The Health Sciences Descriptors (DeCS) were used in an associated way: “Smokers”, “Tobacco Use Disorder”, “COVID-19” and “Complications”. After applying the inclusion criteria, 8 studies remained. The included studies were tabulated and critical and corroborative reviews were made between each of them. Smoking increases the risk of complications from numerous diseases, especially cardiovascular diseases, respiratory diseases (bronchitis and emphysema) and several types of cancer, in addition to causing different types of inflammation, impairing the body’s defense mechanisms, which certainly weakens the immune system, making it less able to respond effectively to infections.